Genome-Wide Characterization and Expression Analysis of bZIP Gene Family Under Abiotic Stress in Glycyrrhiza uralensis - Han, Yuxuan; Hou, Zhuoni; He, Qiuling; Zhang, Xuemin; Yan, Kaijing; Han, Ruilian; Liang, Zongsuo (Frontiers in Genetics, 2021)
The bZIP gene family is one of the largest transcription factor families. It plays an important role in plant growth and development, metabolic and environmental response. However, the complete genome-wide investigation of bZIP gene family in Glycyrrhiza uralensis still remains unexplained. In this study, 66 putative bZIP genes in the genome of G.uralensis were identified and their evolutionary classification, physicochemical properties, conserved domain, functional differentiation and the expression level under different stress conditions were further analyzed. All the members were clustered into 13 subfamilies (A - K, M, S). A total of 10 conserved motifs were found in GubZIP proteins. The members from the same subfamily shared highly similar gene structures and conserved domains. Tandem duplication events acted as a major driving force for the evolution of the bZIP gene family in G. uralensis. Cis-acting elements and protein-protein interaction networks showed that GubZIPs in one subfamily involved in multiple functions, while some GubZIPs from different subfamilies may share the same functional category. The miRNA network targeting GubZIPs showed that the regulation at the transcriptional level may affect protein-protein interaction networks. We suspected that domain-mediated interactions may categorize a protein family into subfamilies in G. uralensis. Furthermore, the tissue-specific gene expression patterns of GubZIPs were analyzed using the public RNA-seq data, then quantified their gene expression level under abiotic stress treatments by using qRT-PCR. The results of this study may serve as potential candidates for functional characterization in future.